An Authorisation Policy Management Model in Federations - Vu, Ngoc Cham (H. : ĐHQGHN, 2018)
A federation is usually an alliance of organisations where users from one organisation are trusted to access resources in another organisation. The membership of federations is diverse and continually changing. Federations require distributed and dynamic security policy management to meet these challenges. We propose an authorisation policy management model, FABACD, which simplifies the management of collaborations between organisations. It allows distributed and trusted administrators to adjust the authorisation policies in a resource holding organisation, whilst ensuring that the latter remains in ultimate control. The net result is that a resource’s authorisation system is able to use user credentials built from preexisting attributes issued by any participating organisation, in order to determine a user’s access rights to the various resources, without requiring credentials to be issued that are based on federation specific attributes. The model significantly simplifies the authorisation management process for the resource holding organisation.